Intra-pixel variability in satellite tropospheric NO2 column densities derived from simultaneous spaceborne and airborne observations - Broccardo, Stephen; Heue, Klaus-Peter; Walter, David; Platt, Ulrich (Atmospheric measurement techniques discussions, 2017)
Aircraft measurements of NO2 using an imaging differential optical absorption spectrometer (iDOAS) instrument over the South African Highveld region in August 2007 are presented and compared to satellite measurements from OMI and SCIAMACHY. In-situ aerosol and trace-gas vertical profile measurements, along with aerosol optical thickness and single-scattering albedo measurements from the Aerosol Robotic Network (AERONET), are used to devise scenarios for a radiative-transfer modelling sensitivity study. Uncertainty in the air-mass factor due to variations in the aerosol and NO2 profile shape is constrained, and used to calculate vertical column densities (VCD), which are compared to co-located satellite measurements. The lower spatial resolution of the satellites cannot resolve the detailed plume structures revealed in the aircraft measurements. The airborne DOAS in general measured steeper horizontal gradients and higher peak NO2 vertical column density. Aircraft measurements close to major sources, spatially-averaged to the satellite resolution, indicate NO2 column densities more than twice those measured by the satellite. The agreement between the high-resolution aircraft instrument and the satellite instrument improves with distance from the source. Despite their low spatial resolution, satellite images reveal point sources and plumes that retain their structure for several hundred kilometers downwind.